2022
DOI: 10.1038/s41366-022-01108-0
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood metabolites and rapid postnatal growth as multiple mediators in the prenatal propensity to childhood overweight

Abstract: Background The mechanisms underlying childhood overweight and obesity are poorly known. Here, we investigated the direct and indirect effects of different prenatal exposures on offspring rapid postnatal growth and overweight in childhood, mediated through cord blood metabolites. Additionally, rapid postnatal growth was considered a potential mediator on childhood overweight, alone and sequentially to each metabolite. Methods Within four European birth-coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The data were consistent with findings in a previous western cohort 42 , 43 . Interestingly, however, the unidentified (U) metabolite U8 was found to be correlated with childhood overweight and rapid growth 44 . Moreover, a previous study determined that imidazole propionate is increased in diabetes and associated with dietary patterns and altered microbial ecology, particularly with low Bacteroides 2 enterotype, which has previously been associated with obesity 45 .…”
Section: Discussionmentioning
confidence: 99%
“…The data were consistent with findings in a previous western cohort 42 , 43 . Interestingly, however, the unidentified (U) metabolite U8 was found to be correlated with childhood overweight and rapid growth 44 . Moreover, a previous study determined that imidazole propionate is increased in diabetes and associated with dietary patterns and altered microbial ecology, particularly with low Bacteroides 2 enterotype, which has previously been associated with obesity 45 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis reviewed 22 studies and concluded that umbilical cord blood leptin was inversely associated with adiposity up to 3 years of age (16). In addition, two recent studies provided evidence convincing the involvement of cord blood metabolites (including cholestenone, branched-chain amino acid, and other metabolites) in the tendency to rapid postnatal growth and of rapid postnatal growth in the tendency to childhood overweight (33,34). So far, explorations concerning the relationships between cord blood metabolites and childhood overweight and adiposity were very limited in past research.…”
Section: Discussionmentioning
confidence: 99%